16-36: Analysis of Complications in Anterior versus Inferior Access to the pericardial space in patients with Epicardial Ventricular Tachycardia. (10th June 2016) - Mathew, Shibu; Lemes, Christine; Heeger, Christian-Hendrik; Hayashi, Kentaro; Reißmann, Bruno; Riedl, Johannes; Saguner, Ardan; Maurer, Tilman; Sohns, Christian; Metzner, Andreas; Kuck, Karl-Heinz; Ouyang, Feifan
Abstract: Background: Epicardial- VT Ablations are increasingly performed, but there are still limited information about its safety and complications. The question whether an anterior epicardial puncture compared to an inferior epicardial punctue may reduce potential complications has not been systematically analysed so far. Methods and Results: Complications associated to the epicardial puncture were analysed in 146 patients (51 ± 16.7yrs, 126 male) and in 171 epicardial procedures. In 35/ 171 (20, 47%) procedures an anterior approach and in 136/171(79, 53%) procedures an inferior approach to the pericardial space was performed. In brief access to the pericardial space was gained from a subxiphoid puncture and access was performed under fluroscopic guidance and additional injection of 2 to 5 ml contrast media to verfiy correct position. The inferior approach was performed via fluroscopically guidance in an antererior-posterior view, whereas the anterior epicardial puncture was performed by an anterior-posterior and additional LAO 90° view in order to avoid abdominal organ perforations. Due to the inferior epicardial puncture in one patient (0.7%) a perforation of the right coronary artery (RCA) was seen. In two pts (1, 47%) a perforation of the liver and in another patient (0, 7%) a perforation of the colon was observed. In these three patients the epicardial sheath was inserted via the liver or colon to the epicardial space. No organ perforations were observed due to an anterior epicardial puncture. Conclusions: The risk of potential severe complications in epicardial-VT Ablations is high. But an anterior epicardial approach may reduce potential complciations.